2022
DOI: 10.1038/s41531-022-00416-6
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural but not macrostructural cortical degeneration occurs in Parkinson’s disease with mild cognitive impairment

Abstract: This study aimed to investigate the cortical microstructural/macrostructural degenerative patterns in Parkinson’s disease (PD) patients with mild cognitive impairment (MCI). Overall, 38 PD patients with normal cognition (PD-NC), 38 PD-MCI, and 32 healthy controls (HC) were included. PD-MCI was diagnosed according to the MDS Task Force level II criteria. Cortical microstructural alterations were evaluated with Neurite Orientation Dispersion and Density Imaging. Cortical thickness analyses were derived from T1-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…As aforementioned, DTI is not a common method for evaluating the GM (particularly in the cortex) because detecting the anisotropy of GM anatomy is challenging, which limits the widespread use of standard diffusion anisotropy metrics ( 58 , 59 ). Meanwhile, cortical microstructural alterations were reported to precede morphological changes ( 60 ). Taken together, this finding lends further support to the suggestion that NODDI indices are potentially more sensitive as biomarkers for detecting cortical microstructural changes in ASD.…”
Section: Discussionmentioning
confidence: 99%
“…As aforementioned, DTI is not a common method for evaluating the GM (particularly in the cortex) because detecting the anisotropy of GM anatomy is challenging, which limits the widespread use of standard diffusion anisotropy metrics ( 58 , 59 ). Meanwhile, cortical microstructural alterations were reported to precede morphological changes ( 60 ). Taken together, this finding lends further support to the suggestion that NODDI indices are potentially more sensitive as biomarkers for detecting cortical microstructural changes in ASD.…”
Section: Discussionmentioning
confidence: 99%
“…NODDI allows for the compartmentalization of the diffusion imaging signal in intra- (i.e., axons and dendrites) and extra- (i.e., glia, cerebrospinal fluid) neuritic spaces, leading to estimates of the microstructural complexity of different tissues in the brain [ 131 ]. Notably, NODDI measures have been shown to be more sensitive than standard diffusion tensor imaging measures (e.g., fractional anisotropy) to structural-developmental changes in normative [ 25 , 132 , 133 ] and clinical [ 87 , 88 , 89 , 134 , 135 , 136 , 137 ] samples. Specific NODDI metrics include the free-water isotropic volume fraction (FISO), reflecting the free water volume fraction; the Neurite Density Index (NDI), reflecting the intra-neurite density; and the Orientation Dispersion Index (ODI), reflecting the angular dispersion of neurites.…”
Section: Role Of Neuroimaging In Concussionmentioning
confidence: 99%
“…Likewise, Guo et al 34 have shown that PD patients have decreased ODI in the bilateral nigrostriatal-nigropallidal pathway as well as in the left limbic pathway in comparison to HC. Focusing on the cognitive symptoms in PD patients, Bai et al 35 have demonstrated that reduction in ODI values in the right frontal and bilateral caudate nuclei areas in PD patients with mild cognitive impairment compared to PD patients with normal cognition. Bange et al 36 have reported a positive correlation between the gait rhythm and ISO values in the right SN area.…”
Section: Introductionmentioning
confidence: 99%